ANALISIS TREND PERMINTAAN DAGING SAPI DI KABUPATEN OGAN KOMERING ULU PROVINSI SUMATERA SELATAN (JASEP, 2018)
This study aims to analyze the demand trend of beef in the next 5 years Ogan Komering Ulu Regency or 2021, which was held in December 2016 until May 2017. This research was conducted in Ogan Komering Ulu District, South Sumatera Province. The research method used is literature study method, which is the method used for the type of research using secondary data (review the results of existing studies). The data collected in this research is the time series data of annual secondary data from 2010 to 2016. The results show that, the Analysis of the Beef Demand Trend in Ogan Komering Ulu District for the next 5 years is predicted by method and processing and data analysis using the least square method (least squares method) shows the result of 4,756 Kg / capita / year. Demand increases as the population grows annually.